2017
DOI: 10.1038/srep45168
|View full text |Cite
|
Sign up to set email alerts
|

“Breakthrough” osmosis and unusually high power densities in Pressure-Retarded Osmosis in non-ideally semi-permeable supported membranes

Abstract: Osmosis is the movement of solvent across a membrane induced by a solute-concentration gradient. It is very important for cell biology. Recently, it has started finding technological applications in the emerging processes of Forward Osmosis and Pressure-Retarded Osmosis. They use ultrathin and dense membranes supported mechanically by much thicker porous layers. Until now, these processes have been modelled by assuming the membrane to be ideally-semipermeable. We show theoretically that allowing for even minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…Following the S-K equations given in [8], these can be simplified for FO systems by to omitting the pressure term because there should be no overall pressure drop across the barrier layer. The resulting equations are:…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Following the S-K equations given in [8], these can be simplified for FO systems by to omitting the pressure term because there should be no overall pressure drop across the barrier layer. The resulting equations are:…”
Section: Theorymentioning
confidence: 99%
“…Today it is generally accepted that if PRO is to be commercially viable then it will be necessary to use resources with a higher salinity than seawater, for example brine from a reverse osmosis desalination plant [6,7], but the power output will still be modest. However in a recent purely theoretical paper a thought provoking theoretical analysis by Yaroshchuk [8] suggested that under some conditions and with a membrane displaying 'leakiness' , a 'breakthrough' mode might occur even to the extent that with the appropriate membranes reverse solute diffusion would be eliminated. Indeed there was the prediction that with these appropriate membranes there would be co-current flow of both solvent and solute against a concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the development of novel membranes for PRO has been a subject of interest for researchers in recent years[140][141][142][143][144][145]. More research into PRO and particularly the development of efficient membranes is needed before it can be considered as a viable source of energy recovery for PVRO systems.…”
mentioning
confidence: 99%